Fuzzy Logic and Neural Networks - Alavala, Chennakesava R. ([S.l.] : New Age International Pvt Ltd Publishers, 2009)
In this title, fuzzy logic and neural networks have been discussed in detail through illustrative examples, methods and generic applications. Extensive and carefully selected references is an invaluable resource for further study of fuzzy logic and neural networks. Each chapter is followed by a question bank which is intended to help in the preparation for external examination.
Keywords: Fuzzy logic; Neural networks (Computer science); Neuronnät (datorer)